Оrganoprotective efficiency of eprosartan in patients with chronic glomerulonephritis - Ye. V. Kalyuzhina; L. G. Sourkova; M. A. Solovtsov; D. I. Konaplev; V. V. Kalyuzhin (Бюллетень сибирской медицины, 2007)
The 12-week open uncontrollable study of eprosartan organoprotective efficacy was performed in 15 patients with chronic glomerulonephritis. Study results showed high organoprotective efficacy of eprosartan, prescribed in a dose of 600 mg daily, which is expressed as anti-proteinuric, anti-hematuric actions, positive dynamics of intraglomerular hemodynamics parameters, decreased left ventricular hypertrophy and stiffness and also normalized vasomotoric functions of brachial artery endothelium.